Review of Hillel Schwartz. 2011. Making Noise: From Babel to the Big Bang and Beyond. Brooklyn: Zone Books - Mattern, Shannon (Current Musicology, 2012)
Hillel Schwartz’s Making Noise: From Babel to the Big Bang and Beyond is not merely a text to be read; it’s also an object to be grappled with. One must create space for it, adopt a proper reading posture to accommodate it, and listen to it—both to the words on the pages and to the pages themselves. At 9 ¼ in. x 6 ¼ in. x 2 3/8 in., Making Noise is not the kind of book one can easily tuck into a bag for subway reading. In fact, in the two months I spent working through the text, not once did I manage to find sufficient spare space in my bag to lug it to school or to a coffee shop; consequently, I read the book entirely in my apartment—in a familiar and relatively quiet acoustic environment, which may have set Schwartz’s babble and bang into acoustic relief. In addition, Making Noise is not the kind of book one can easily read while lying on the couch; its 2.5 pounds tired my wrists far too quickly. As a result, I read the entire book sitting or standing up, or while lying on my stomach on the living room carpet. I never experienced Schwartz with my head cocooned in a pillow, down and cloth providing acoustic insulation. Consequently, as I read, I became more conscious of the symphony of white noises—humming refrigerators and whirring hard drives—filling my seemingly quiet Brooklyn apartment.